CARA WIMBA DAN TATA UNGKAPAN BAHASA RUPA DALAM PRINT-AD SEBAGAI STRATEGI KOMUNIKASI Studi Kasus Iklan Pemenang The Cannes Lions International Festival of Creativity Kategori Print-Ad pada tahun 1992 - Dewi, Agustina Kusuma; Surahman, Adi (ISI Press Institut Seni Indonesia Surakarta, 2023)
There are many advertisements whose visual expressions are dominated by Western fine arts and graphic design techniques (which tend to be one of the patrons of graphic design scholarship in Indonesia, so it requires significant exploration and development of traditional art roots to be able to find ideas about Indonesian graphic design. Wimba Method and Visual Language Expression is a wealth of world visual language, in this research it is used as a reference for visual styles based on local Indonesian traditions. Using a descriptive qualitative approach with a digital survey as a research instrument, the research objects were 43 advertisements that were winners in the print-ads category in The Cannes Lions International Festival of Creativity in 1992 (the first year the Press and Outdoor Lions category appeared). From the research results, it was concluded that visual style has the impact of providing stimuli to the target audience to determine the priority of information to be accessed; where there is a tendency, determination This begins first from an affective point of view, rather than a cognitive one.